2012
DOI: 10.4172/2167-0374.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Healthy, but are they Satisfied? Factors Associated with Job Satisfaction in Professional Soldiers of the Slovenian Armed Forces

Abstract: Aim: To identify factors associated with job satisfaction in professional soldiers of the Slovenian Armed Forces using demographic characteristics, burnout, personality traits, and health and working environment characteristics. Method: 361 military personnel (317 male (87.8%), 44 female (12.2%)) participated in a cross-sectional study (80.6% response rate). Sample data was presented by frequency and percentage distribution for categorical variables, or by mean value and standard deviation for continuous varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…However, the authors did not distinguish any differences between clinical settings, and only tried to compare the size of the hospital (Mijakovski et al 2011). A group of Slovenian authors reported a high level of EE (46%) in a sample of family medicine trainees, which correlated with the findings of Ožvačić-Adžić et al, but they also found a high level of DP (42.4%) and a low level of PA (15.2%), which does not correlate with the reviewed studies (Selič et al 2012, Ožvačić-Adžić et al 2013). Selič et al did not find any relationship between the MBI dimensions and gender, which was also shown in our study (Selič et al 2012).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the authors did not distinguish any differences between clinical settings, and only tried to compare the size of the hospital (Mijakovski et al 2011). A group of Slovenian authors reported a high level of EE (46%) in a sample of family medicine trainees, which correlated with the findings of Ožvačić-Adžić et al, but they also found a high level of DP (42.4%) and a low level of PA (15.2%), which does not correlate with the reviewed studies (Selič et al 2012, Ožvačić-Adžić et al 2013). Selič et al did not find any relationship between the MBI dimensions and gender, which was also shown in our study (Selič et al 2012).…”
Section: Discussionmentioning
confidence: 70%
“…In Slovenia, Selič et al conducted a cross-sectional study of Slovenian family medicine trainees, nearly every fifth (18.3%) scored high in all three dimensions (Selic et al 2012). There is insufficient understanding of job satisfaction as a crucial factor in the development of burnout, and a need for more detailed research (Selič et al 2012). Prevention of burnout syndrome should be a priority for multiple stakeholders in the healthcare system, and all levels of management must be involved in order to reduce its prevalence and prevent its effects on nurses, healthcare workers and the overall system (Moss & Kleinpell 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In one of our previous studies on Slovenian Armed Forces members, longer sick leave duration was found in female soldiers (26) and a negative association between satisfaction with co-workers and female gender was identified (39). It was suggested that special attention should be given to female soldiers when planning supervision, work procedures, and the gender equality policy of the Armed Forces (39). However, in present study, female gender was not identified to be significantly associated with variables of interest, which is probably due to the low proportion of women in the surveyed group.…”
Section: Discussionmentioning
confidence: 84%
“…Both depression and anxiety are known to be more prevalent in women (37,38), but in our study female gender was not shown to be significantly associated with either the SDS or SAS score (Table 3) or with the co-occurrence of depression and anxiety (Table 4). In one of our previous studies on Slovenian Armed Forces members, longer sick leave duration was found in female soldiers (26) and a negative association between satisfaction with co-workers and female gender was identified (39). It was suggested that special attention should be given to female soldiers when planning supervision, work procedures, and the gender equality policy of the Armed Forces (39).…”
Section: Discussionmentioning
confidence: 95%
“…A cross-sectional study performed in 2011 in Slovenia showed a significantly higher prevalence of chronic diseases in those with a lower socio-economic status and in pensioners [ 58 ]. Since level of education has been shown to be associated with socioeconomic status in the Slovenian active population [ 59 ], the explanation could lie partially in this characteristic. Selic and co-workers [ 60 ] reported the burden of somatic co-morbidity to be smaller than the impact of psychosocial determinants when identifying the patterns of physical co-morbidity and factors associated with the onset of depression.…”
Section: Discussionmentioning
confidence: 99%